PENGARUH TATA KELOLA ADMINISTRASI DESA TERHADAP TINGKAT KEPUASAN MASYARAKAT DI DESA UMPUNGENG, KECAMATAN LALABATA, KABUPATEN SOPPENG - Dwijayanti, Rifalni; Muhammadiah, Muhammadiah; Malik, Ihyani (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
This research aims to evaluate the influence of governance on the level of community satisfaction in Umpungeng Village. Utilizing quantitative methods, the results demonstrate that the impact of governance can be categorized as highly positive. Respondent analysis reveals that the reliability variable scores at 81%, while the independence variable scores at 70%. Through simple linear regression analysis, it was identified that variables X4 (responsibility) and Y4 (assurance) exert a strong influence, with an F value of 21.462 and a significance level of 0.000. These findings support the acceptance of the alternative hypothesis (H1) and the rejection of the null hypothesis (H0). In the regression equation, the constant value is 8.061, and the responsibility value (X4) is 0.553. Further analysis indicates that the independence variable (X4) holds a notably strong influence, with a Beta Standardized Coefficients value of 0.81 or 81%. The conclusion drawn from this research is that governance significantly impacts community satisfaction, particularly when associated with physical aspects.